Efficient nursery plant production of dwarf cogongrass (lmperata cylindrica L.) through mass propagation in liquid culture - Nafiatul Umami, N. Umami (Grassland Science, 2012)
Dwarf cogongrass (Imperata cylindrica L.) was developed as a dwarf mutant through hear,y-ion beam irradiation 7 years ago. The dwarf mutant could be expected to use as a new variety for a cover plant with low maintenance, although it has poor seed fertility. To establish an effrcient nursery production system for dwarf cogongrass, we attempted mass propagation of it in liquid culture and investigated the genetic stabitity of its regenerants. Multiple-shoot clumps (MSCs) were initiated from apical meristems of dwarf cogongrass on Murashige and Skoog (MS) solid medium supplemented with 0.1 mgL-t 2,4- dichlorophenoxyacetic acid (2,4-D) and 2.0 mg L t benzylaminopurine (BAp). Mass propagation conditions were established from MSCs cultured in MS Iiquid medium containing 0.05 mg L-l 2,4-D and 0.5 mg L 1 BAp. The fresh weight of the MSCs per flask increased by more than 16 times in 14 days of liquid culture. Two different sizes of MSCs were produced in liquid curture. when smaller MSCs (<2 mm in diameter) were transferred to half-strength hormone-free MS solid medium, plant regeneration occurred at high fiequency (93.3vo). These tissues showed high regenerative potential with approximately 350 green shoots recovered within 50 days from 60 regenerating clumps. Furthermore, root elongation was vigorous in the regenerants growing in the same medium. Regenerated plants were acclimatized in hydrated )iS,-7 pellets for 30 days and then grown in soil as nursery plants. The plant height of regenerants was almost the same as original dwarf cogongrass and significantly lower than the wild qpe plants (P < 0.01). Analysis of amplified fragment length polymorphism (AFLP) banding patterns generated using 10 primer combinations showed no major genetic variations among the regenerated plants and original dwarf cogongrass.